Predict the effectiveness of academic information system Based on the components of strategic intelligence - Keikha, Alemeh; Zamani, Bibi Eshrat (International Journal of Education and Cognitive Sciences, 2022)
Introduction: Strategic intelligence is a novel theory concerning organization issue for finding basic capabilities and competitive advantages in present unstable organizational environment. Intelligence process converts information and makes intelligence. This process is done through analysis, interpretation, composition and application of information in the future decision making of organizations so the purpose of the present study is Predicting the effectiveness of academic information system Based on the components of strategic intelligence in university of zabol.Materials and method: Strategic Intelligence questionnaire and standardized questionnaire for Effectiveness of Information Systems were employed for assessment.Results: Finding reveals that there is a significant correlation between variables and also effectiveness of management information system and its components can be predicted by strategic intelligence.Conclusion: Results indicated that high strategic intelligence leads to the effectiveness of academic information which give competitive advantage to the organization and also deliver a product or service that is at a lower cost.